The Power of Philosophy Thought and Redemption - Roy, Kaustuv (Springer International Publishing, 2018)
This book explores the possibility of philosophical praxis by weaving an ontological thread through four principal thinkers: Heidegger, Schelling, Goethe, and Heraclitus. It argues that a special kind of redemptive power awaits the structural understanding of thought that is beyond semantic formations such as concepts and ideational systems. The author claims that the "power" is negative in nature, trans-personal, and derived directly from the understanding of thought as a structural pulse. The book travels backwards in time, encountering successively Heidegger's critique of calculative thinking, Schelling's Mind/Nature relation, Goethe's Delicate Empiricism, and the aphoristic wisdom of Heraclitus in search of a redemptive power that lies in the self-knowledge of thought. This power is ontological and not historical or developmental; it is the same at all times and all points of history. The author refers to the praxis as "philosophical bilingualism.".